2023
DOI: 10.3390/jcm12020475
|View full text |Cite
|
Sign up to set email alerts
|

Parental Resources in Parents of Children with Special Needs (SNs) at the Time of COVID-19

Abstract: Background. The limitations imposed by governments for containing the spread of COVID-19 have affected familial relationships, especially those of families dealing with children with special needs or chronic illness conditions. The current study aims to better understand what pathological/disability condition has impacted parental resources, sense of competence, and perception of children’s executive functioning the most. Methods. A sample of 648 parents was asked to answer a survey assessing children’s condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The disruption caused by the COVID‐19 pandemic to people's daily routine, which included social distancing and school closures, was found to be challenging for parents of typically developing children (Laufer & Shechory‐Bitton, 2021) but unsurprisingly seemed to be even more challenging for parents of children with special needs (Pecor et al, 2021; Ueda et al, 2021). Parents of children with disabilities who already experienced significant challenges due to their child's disability were forced to adapt to the sudden stoppage of school and necessary services, alongside social distance restrictions that cut them off from social support resources (Gentile et al, 2023). The majority of parents reported that this period required more commitment than before, included more difficulties in managing their children's daily activities, and worsened the children's behavioural problems (Ameis et al, 2020; Colizzi et al, 2020; Ersoy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disruption caused by the COVID‐19 pandemic to people's daily routine, which included social distancing and school closures, was found to be challenging for parents of typically developing children (Laufer & Shechory‐Bitton, 2021) but unsurprisingly seemed to be even more challenging for parents of children with special needs (Pecor et al, 2021; Ueda et al, 2021). Parents of children with disabilities who already experienced significant challenges due to their child's disability were forced to adapt to the sudden stoppage of school and necessary services, alongside social distance restrictions that cut them off from social support resources (Gentile et al, 2023). The majority of parents reported that this period required more commitment than before, included more difficulties in managing their children's daily activities, and worsened the children's behavioural problems (Ameis et al, 2020; Colizzi et al, 2020; Ersoy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of parents reported that this period required more commitment than before, included more difficulties in managing their children's daily activities, and worsened the children's behavioural problems (Ameis et al, 2020; Colizzi et al, 2020; Ersoy et al, 2020). This added stress was found to be associated with lower mental health, well‐being, and quality of life (QoL), which were more noted among parents of children with special needs than among parents of typically developing children (Gentile et al, 2023; Pecor et al, 2021; Ueda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%